ASSESSMENT OF INTESTINAL PARASITIC CONTAMINATION AND FOOD SAFETY PRACTICES AMONG FRUIT AND VEGETABLE VENDORS IN KANO - Maaji, Sunusi Usman; Sani, Faruk (FUDMA Journal of Sciences, 2026)
Intestinal parasitic infections remain a significant public health concern in developing countries, often transmitted through the consumption of contaminated raw fruits and vegetables. This study investigated the prevalence of intestinal parasites in 160 fruit and vegetable samples collected from three major markets in Kano Metropolis, Nigeria: Kasuwar Yankaba, Kasuwar Naibawa Yanlemu, and Kasuwar Tarauni. Using standard parasitological techniques, an overall contamination rate of 8.7% was observed. Ascaris lumbricoides was the most frequently identified parasite (3.1%), followed by Strongyloides stercoralis (2.5%) and Entamoeba histolytica (2.5%). Contamination rates varied significantly by produce type (p = 0.026), with tomatoes, carrots, and cabbage showing the highest prevalence (15% each). Furthermore, the study assessed vendor awareness and practices, revealing that while 51.3% were aware of parasitic risks, 76.9% utilized well water for washing produce. These findings underscore the urgent need for enhanced food safety regulations and hygiene education for vendors to mitigate the risk of foodborne parasitic diseases in urban Nigerian settings.